Epidemiology of Contact Lens–Related Emergency Department Visits: Data From Nationwide Emergency Department Sample. Issue 5 (4th May 2023) - Usmani, Bushra; Dayananda, Sanjana; Shah, Syed; Jhanji, Vishal
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this retrospective longitudinal cohort study was to determine the epidemiology of contact lens‐related visits to the emergency department at a national level and identify high-risk groups. Methods: National emergency department (ED) sample, a representative sample of all US EDs, was used to determine the incidence and characteristics of keratitis in contact lens users presenting to the ED from 2006 to 2017. ICD-9-CM and ICD-10-CM codes for corneal disorder due to contact lens use (371.82 and H1882) were used to identify the patients. Results: A total of 149, 716 ED visits were recorded with a diagnosis of corneal disorder due to contact lens use. Incidence of ED visits with contact lens–related corneal disorder declined steadily from 2010 to 2016. In total, 67% of the patients were female, 68.9% were adults aged 19 to 44 years, and 56.3% had a private insurance provider. The most common diagnosis at the time of discharge was "eye discharge" or "redness" (10.9%), followed by "corneal ulcer" (3.6%). Patients of highest income quartiles were more likely to present to the ED with contact lens–related corneal disorders (adjusted odds ratio, 1.21, 95% confidence interval 1.15–1.27) compared with low-income quartile. Among those who were discharged from the ED, the average charge per patient was 1051.4 (SD = 795.4). Conclusions: Women, young adults, and patients belonging to higher socioeconomic status were found to have higher prevalence of contact lens–related corneal ED visits. Identification of high-risk groups will help in the prevention of further corneal complications and the associated vision loss.